2022
DOI: 10.3389/fnmol.2022.901953
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia ulmoides Olive Male Flower Extracts Ameliorate Alzheimer’s Disease-Like Pathology in Zebrafish via Regulating Autophagy, Acetylcholinesterase, and the Dopamine Transporter

Abstract: Alzheimer’s disease (AD) is the most prevalent neural disorder. However, the therapeutic agents for AD are limited. Eucommia ulmoides Olive (EUO) is widely used as a traditional Chinese herb to treat various neurodegenerative disorders. Therefore, we investigated whether the extracts of EUO male flower (EUMF) have therapeutic effects against AD. We focused on the flavonoids of EUMF and identified the composition using a targeted HPLC-MS analysis. As a result, 125 flavonoids and flavanols, 32 flavanones, 22 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Intriguingly, olive was shown to effectively restore mitochondrial complex activities and maintain their redox state. Researchers have indicated that the administration of olive exhibits a high propensity to offer neuroprotection against neurotoxicants and other neurodegenerative ailments, such as Parkinson's disease [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, olive was shown to effectively restore mitochondrial complex activities and maintain their redox state. Researchers have indicated that the administration of olive exhibits a high propensity to offer neuroprotection against neurotoxicants and other neurodegenerative ailments, such as Parkinson's disease [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%